Optimizing CI/CD Pipelines for Multi-Cloud Environments: Strategies for AWS and Azure Integration - Koneru, Naga Murali Krishna (Eastasouth Institute, 2025)
CI/CD pipelines are essential for modern software development to speed up application delivery and ensure reliability. However, organizations experience considerable management difficulties when they operate Continuous Integration and Deployment workflows between AWS and Azure. The research discusses multiple approaches to optimizing CI/CD pipelines and demonstrates their integration between AWS and Azure systems. The complete implementation guidelines within the method include selecting tools and best practices along with the necessary architectural elements to construct secure, scalable, and successful CI/CD pipelines. Success in deployment requires using standardized CI/CD platforms, infrastructure code implementation, and security platforms spanning multiple cloud environments, price reduction technologies, and consolidated monitoring tools. The deployment process framework integrates cloud platforms by implementing a solution that merges interoperability and security management alongside cost control functions. This proposal demonstrates its worth by applying the example project to prove significant benefits: fast deployment speed, lower costs, and dependable system infrastructure. The document explores actual applications of optimized pipelines, which decrease operational complexity and enhance resource utilization efficiency. The report includes deployment guidelines supplemented by practical examples to guide organizations during their adoption phase. Standardized CI/CD management approaches allow organizations to simplify deployment pipelines and automate workflow processes during multi-cloud connectivity risk management. The surveyed findings regarding optimizing AWS and Azure CI/CD workflows enable organizations to improve their DevOps performance in complex cloud infrastructure.